Analisis Faktor-Faktor Penentu Minat Mahasiswa dalam Memilih Program Studi Pendidikan Teknologi Informasi Universitas Muhammadiyah Sukabumi - Juniar, Ambara Iswari; Aziz, Muhammad Thariq; Rahmat, Dadan (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
This study aims to determine and analyze the factors that determine students' interest in choosing the Information Technology Education Study Program at Muhammadiyah University of Sukabumi. The research method used is quantitative research with the type of field research. The sample in this study amounted to 52 respondents. The data collection technique was carried out through a questionnaire. Based on the results of the study, it is known that the factor that determines students' interest in choosing the Information Technology Education Study Program is the self-motivation factor (X2) with a significance value of 0.000 (<0.05). This means that Ha is accepted and H₀ is rejected, so it can be concluded that self-motivation has a significant influence on students' interest in choosing the Information Technology Education Study Program. Meanwhile, the other five variables do not show a statistically significant influence because they have a significance value greater than 0.05. In detail, the Student Ability variable (X1) has a significance value of 0.790, Study Program Excellence (X3) of 0.251, Parental Influence (X4) of 0.304, Peers (X5) of 0.460, and Social Media (X6) of 0.912. Thus, it can be concluded that internal factors in the form of self-motivation are the dominant factors that influence student interest in choosing the Information Technology Education Study Program at Muhammadiyah University of Sukabumi. It is recommended that the Information Technology Education Study Program continue to improve the quality, student confidence, and the attractiveness of the study program to maintain and increase the interest of prospective students in the future.